Ansiedad y respuesta fisiológica de pacientes pediatricos en relación a la presencia de sus tutores previo a la consulta odontológica - Dayanna del Cisne, Granda Ortiz (2021)
ABSTRACT This research determines the existing relationship between anxiety and physiological responses from pediatric patients who receive dental checkup for their first time in UNACH’s Dental Care Department. It involved tutors’ presence or absence. The type of research is descriptive observational and transversal. It is based on a mixed approach (qualitative-quantitative). The sample was made up of 114 patients from six to nine years old. They were divided into two homogeneous groups. To determine their anxiety level, a Venham's test was applied whereas the oxygen saturation in the blood was recorded at their clinical index cards in order to evaluate them later. Those were part of the Promotion and Prevention in the program. The obtained results showed a direct relationship between the levels of anxiety and the studied groups at a level of P ≤ 0.05 compared to the variable of physiological response in spite of being within a normal level of oxygen saturation in the blood, their values are different. Meanwhile the statistical correlation determined by Sperman's Rho correlation coefficients, showed that the relationship values between the study variables were between 0. 432 and 0.449, it represents an average positive correlation in contrast to ranges. It can be concluded that the presence or absence of the tutors in their first dental consultation affects patients’ anxiety levels. Keywords: Anxiety, Pediatric Dentistry, Venham Test. Translation reviewed by: Msc. Elizabeth Diaz English professor 0603277765